2017
DOI: 10.1177/1368430217695442
|View full text |Cite
|
Sign up to set email alerts
|

Anger as a catalyst for change? Incremental beliefs and anger’s constructive effects in conflict

Abstract: Anger is often seen as a destructive emotion in intergroup conflict, causing aggressive behavior that escalates conflicts (Cheung-Blunden & Blunden, 2008; Huddy, Feldman, & Cassese, 2007). However, a growing body of interpersonal and intergroup psychological research has begun to challenge this view. Drawing from the perspective that emotions can elicit multiple situation-dependent behaviors to achieve identical emotional goals, this research has shown that anger can lead to conciliatory behaviors in specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…This starkly opposes the predictions we would expect of the inefficacy claim, and suggests that anger communication has an important role to play in inter-group conflict resolution. Mounting evidence supports the main finding of this study, as anger communication has been observed to increase dominant group support for conciliatory policies in the context of the Israel-Palestine conflict, US race-relations (Shuman et al, 2018), and cases of xenophobia (de Vos et al, 2013). The Out-group Reason for holding the inefficacy claim is therefore challenged by evidence that the communication of anger from a disadvantaged group often actually increases dominant group support for conciliatory policies.…”
Section: The Out-group Reasonsupporting
confidence: 83%
“…This starkly opposes the predictions we would expect of the inefficacy claim, and suggests that anger communication has an important role to play in inter-group conflict resolution. Mounting evidence supports the main finding of this study, as anger communication has been observed to increase dominant group support for conciliatory policies in the context of the Israel-Palestine conflict, US race-relations (Shuman et al, 2018), and cases of xenophobia (de Vos et al, 2013). The Out-group Reason for holding the inefficacy claim is therefore challenged by evidence that the communication of anger from a disadvantaged group often actually increases dominant group support for conciliatory policies.…”
Section: The Out-group Reasonsupporting
confidence: 83%
“…This study suggests that anger communication, even when aggressive, can recruit support, as opposed to inspiring defensiveness and retaliation. Mounting evidence supports the main finding of this study, as anger communication has been observed to increase dominant group support for conciliatory policies in the context of the Israel–Palestine conflict, US race‐relations, and cases of xenophobia (de Vos, van Zomeren, Gordijn, & Postmes, 2013; Shuman, Halperin, & Reifen Tagar, 2018).…”
Section: The Orthodox View Challengedsupporting
confidence: 82%
“…beliefs in protracted conflicts (e.g., Shuman, Halperin, and Reifen Tagar 2018) including hope (Leshem 2019). Last, holding all else constant, it appears that Jewish Israelis and Palestinians have similar wishes for reciprocal peace but that Palestinians' expectations for reciprocal peace are still significantly higher.…”
Section: Predicting Hope For Peacementioning
confidence: 96%
“…However, Wald’s tests comparing effect sizes reveal that the effects of political ideology on citizens’ wishes and expectations for peace are always smaller than the effects of appraisals (effect on wish: AWA > EOC, F = 20.1, p < .001, AEA > EOC, F = 3.2, p = .07; effects on expectation: AWA > EOC, F = 28.4, p < .001, AEA > EOC, F = 41, p < .001). 4 This point should be highlighted because political ideology is frequently cited as one of the most robust predictors of conflict-related beliefs in protracted conflicts (e.g., Shuman, Halperin, and Reifen Tagar 2018) including hope (Leshem 2019). Last, holding all else constant, it appears that Jewish Israelis and Palestinians have similar wishes for reciprocal peace but that Palestinians’ expectations for reciprocal peace are still significantly higher.…”
Section: Predicting Hope For Peacementioning
confidence: 99%